A review of some upper air analyses in relation to prediction of Nor'westers (MAUSAM, 1955)
Standard upper air analyses, such as delineation of thermal thickness patterns on isobaric  surface,    computation of development', vertical component of absolute vorticity of geostrophic winds and horizontal wind velocity convergence were made in relation to the nor'wester thunderstorms over northeast India and East Pakistan. For the thickness analysis, the special Dine's meteorograph observations taken in April 1944 at shorter intervals of  time and from a closer network of stations than in 1953 were used, while all the above-mentioned analysis were made for eight consecutive days in May 1953. No significant medium-range prognostic value was found in any of the analyses based on the available network of radiosonde and upper wind data for forecasting the nor'westers 12 to 36 hours ahead of their actual occurrence. Nevertheless, the partial thickness patterns of the 700/500 mb-layer, the field of 'development' and the lower level wind velocity convergence, based on the evening data for a particular day, appeared to influence the nor'wester development on the same evening and night.